Inside or outside?: expanding the narratives about life-sentenced prisoners - Herbert, Steven Kelly (Punishment & society, 2018)
The number of life-sentenced prisoners in the United States is growing, an increase that deserves ongoing critical consideration. Such consideration is heightened by the fact that many lifers undergo significant personal transformations during their incarceration. This paper uses interviews with 21 life-sentenced prisoners in the state of Washington to document the degree of such transformations. These transformations create compelling questions for theoretical strains in the sociology of punishment that draw upon the seminal work of Durkheim. Further, those transformations deserve greater consideration as the politics and practices of incarceration continue to unfold in the United States.